Revolutionizing Patient Care: A Comprehensive Review of Recent Advances in Flexible Printed Heaters for Wearable Medical Applications - Hundessa Daba Nemomssa; Frederick Bossuyt; Bjorn Vandecasteele; Herbert De Pauw; Netsanet Workneh Gidi; Pieter Bauwens (Actuators)
Recent developments in flexible printed heaters (FPHs) for wearable thermal applications, driven by the advancement of printed electronics, show great promise in revolutionizing patient care through the development of wearable flexible heaters for medical applications. Wearable heaters with high thermal stability, heat uniformity, safety, flexibility, comfort, biocompatibility, biodegradability, recyclability, and power efficiency are desirable for standalone medical thermotherapy applications. This paper reviews recent advancements in the design of FPHs for wearable thermal applications. Materials used in the FPHs, fabrication methods, design considerations, temperature control mechanisms, medical applications, and performance analysis of specific FPHs are all thoroughly discussed. Materials used in FPHs, such as conductive and substrate materials, receive special attention along with the heater design parameters. Additionally, the paper addresses the challenges and future directions for the advancement of FPHs in wearable medical applications.